(untitled) (Impetus, 2021)
“Sociomotricidad and capital body: an educational bet of Edufines program for sociability of people with functional diversity (people with disabilities)”. This article visualizes an epistemic construction with some theoretical and experiential contributions. These have been produced during the researcher’s life and her co-researchers through their 24 years in the program, based on a qualitative study with a narrative perspective (biographical partner) from life stories reconstructed with the support of the studied population, their families and teachers, believing in the description and understanding these contributions. At the end, the annexes and conclusions of the analysis presented as a result of this investigation and these are taken as a reference to continue in the construction and progress of other researches, in addition of being a reference point for those involved in the training process of the population with functional diversity which propose to be seen and projected from a pedagogical view, strengthening its capital body with a structure full of meanings and social representations remodeling the human being from and to the development of civic competences or process of ciudadanización.